Identifying Effective Halal Attributes for Muslim Tourists in Japan: Perspectives from Supply and Demand - Ghimire, Anil (ASEAN Journal on Hospitality and Tourism, 2025)
Halal tourism is growing for Muslim and non-Muslim destinations due to Muslim population growth. Halal tourism is harder in non-Muslim countries due to cultural differences. Previous research investigated halal attributes from the perspective of the demand side. This study investigated Japan's halal attributes from the perspectives of supply and demand, as perceived by destination Muslim residents and Muslim tourists, thereby promoting halal tourism in non-Muslim destinations. The viewpoints of Muslim residents identified four important halal attributes: supportive infra and service, social environment, halal food and beverage, and specific facilities and amenities. The effectiveness of these attributes was confirmed by 253 Muslim tourists. It was found that the success of a non-Muslim destination in halal marketing is contingent on partial halal resources and well-managed indigenous resources.